Behavioral Assessment and Treatment of Aerophagia. (June 2022) - Cengher, Mirela; Strohmeier, Craig W.
Aerophagia is characterized by excessive air swallowing and can have serious negative effects on one's health. We present the assessment and treatment of a 16-year-old girl, Khloe, with developmental disabilities and aerophagia. The initial assessment indicated that aerophagia occurred primarily to access attention in a divided attention context; however, our function-based treatment did not result in a clinically significant reduction in problem behavior. We then conducted a second assessment that indicated that Khloe's aerophagia indeed occurred primarily in a divided attention context, but that it persisted independent of social consequences. We concluded that the divided attention context served as a motivating variable for aerophagia. Our second treatment consisted of differential reinforcement of other behavior, noncontingent access to competing stimuli, and graduated exposure to contextual variables (i.e., people and divided attention) that occasioned aerophagia. The treatment was successful in reducing rates of aerophagia. We discuss implications for assessment and treatment, as well as recommendations for clinicians and students.